2014
DOI: 10.1177/000313481408000619
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regionalization of Pancreaticoduodenectomy for Pancreatic Cancer in North Carolina since 2004

Abstract: Pancreaticoduodenectomy (PD) carries a significant risk. High-volume centers (HVCs) provide improved outcomes and regionalization is advocated. Rapid regionalization could, however, have detrimental effects. North Carolina has multiple HVCs, including an additional HVC added in late 2006. We investigated regionalization of PD and its effects before, and after, the establishment of this fourth HVC. The North Carolina Hospital Discharge Database was queried for all PDs performed during 2004 to 2006 and 2007 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Regionalization of hepatobiliary surgery in the United States beginning in 2000 led to a 40% lower operative mortality rate 27 ; natural regionalization of pancreatic surgery was associated with lower mortality in Maryland 28 but not in North Carolina. 29 There have been no clinical trials of interventions to regionalize surgery. We also found a mortality difference before and after regionalization, similar to previous studies, but our interrupted time series analysis was able to distinguish the effect of regionalization on outcomes from other confounding exposures, such as improvements in the quality and outcomes of care over time.…”
Section: Discussionmentioning
confidence: 99%
“…Regionalization of hepatobiliary surgery in the United States beginning in 2000 led to a 40% lower operative mortality rate 27 ; natural regionalization of pancreatic surgery was associated with lower mortality in Maryland 28 but not in North Carolina. 29 There have been no clinical trials of interventions to regionalize surgery. We also found a mortality difference before and after regionalization, similar to previous studies, but our interrupted time series analysis was able to distinguish the effect of regionalization on outcomes from other confounding exposures, such as improvements in the quality and outcomes of care over time.…”
Section: Discussionmentioning
confidence: 99%
“…Centralization of PD to high-volume centers collaborating within oncology networks might bring a solution as long as high-quality care is guaranteed. Within the described GIOCA collaboration, the 30-day and 90-day mortality is within the range of other high-volume centers, which has been reported to be 0–3.8% versus 4.3–7.3%, respectively [2, 2225].…”
Section: Discussionmentioning
confidence: 84%
“…Centralisation of pancreatic surgical services has led to improved outcomes including higher resection rates [ 7 , 8 ], lower operative mortality [ 9 , 10 ] and improved long-term survival [ 11 ]. Similar improvements with centralisation have been noted for liver [ 12 ], oesophageal [ 13 ], complex urological [ 14 ] and vascular surgery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings the population benefits of regionalisation are more difficult to demonstrate. Although studies using hospital data have demonstrated improved outcomes associated with centralisation of surgical services for patients who receive treatment [ 8 , 16 , 17 ], these studies may be biased by selection of patients at the regional centres and do not take into account patients who are not referred for treatment. Studies demonstrating improved population outcomes as a result of regionalisation of complex surgery are more difficult to undertake.…”
Section: Discussionmentioning
confidence: 99%